The Role of Public Green Open Space in Supporting Urban Sustainability: a Case Study of Ahmad Yani Park, Gajahmada Park, and Usu Urban Forest in Medan City - Ramayani. M; Ruri Prihatini Lubis; Ruth Riah Ate Tarigan (CV. Doki Course and Training, 2026)
This study discusses the sustainability performance of public green open space (RTH) in Medan City through an integrated approach that includes environmental quality, social quality, and accessibility. The methods used include regression analysis, correlation, and ANOVA to test the influence of each variable on urban sustainability. The results showed that these three variables had a significant effect, with the regression model able to explain 68.4% of the sustainability variance. Social quality was the most dominant factor (β = 0.412; r = 0.74), followed by environmental quality (r = 0.68) and accessibility (r = 0.61). Spatially, USU Urban Forest shows the highest ecological performance with a canopy cover of 78%, an NDVI value of 0.72, and a lower average microclimate temperature (27.1°C) compared to Ahmad Yani Park (29.3°C) and Gajah Mada Park (30.1°C). However, Taman Ahmad Yani obtained the highest overall sustainability score (85/100) because it was supported by superior social perception (4.35) and accessibility (4.60). Meanwhile, Taman Gajah Mada showed moderate performance (75.3/100), and USU Urban Forest received a lower score (70/100) due to limited facilities and access range. The results of the ANOVA test showed a significant difference between locations (Sig = 0.000), which indicates that the Green Open Space typology affects sustainability. Ahmad Yani Park tends to excel in social and accessibility aspects, while USU's urban forests play a greater role in ecological stability. This study confirms that the sustainability of urban RTH will be optimal if ecological, social, and accessibility functions are developed synergistically and not partially.